2010
DOI: 10.1590/s1413-86702010000200003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical signs, diagnosis, and case reports of Vaccinia virus infections

Abstract: We declare no confl ict of interest. ABSTRACTVaccinia virus is responsible for a zoonosis that usually affects cattle and human beings in Brazil. The initial clinical signs of the infection are focal red skin areas, fever, and general symptoms similar to those of a cold. Then, pustules and ulcerated lesions surrounded by edema and erythema follow, as well as local lymphadenopathy that can last for weeks. Cure and healing of the lesions occur over several weeks, leaving a typical scar in the skin of people and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…However, the association is not absolute, with DPP21 and DPP17 falling elsewhere within the "Dryvax cluster." It is also curious that horsepox virus falls into this grouping, providing some support for the hypothesis that HSPV derives from a feral vaccine strain (33) in much the same manner as VACV appears to have established new zoonotic infections in Asian water buffalo and South American cattle (4,30). It has previously been noted that there is more sequence diversity among all the sequenced VACV strains (including Tian Tan and Copenhagen) than among extant variola virus strains (24).…”
Section: Downloaded Frommentioning
confidence: 93%
“…However, the association is not absolute, with DPP21 and DPP17 falling elsewhere within the "Dryvax cluster." It is also curious that horsepox virus falls into this grouping, providing some support for the hypothesis that HSPV derives from a feral vaccine strain (33) in much the same manner as VACV appears to have established new zoonotic infections in Asian water buffalo and South American cattle (4,30). It has previously been noted that there is more sequence diversity among all the sequenced VACV strains (including Tian Tan and Copenhagen) than among extant variola virus strains (24).…”
Section: Downloaded Frommentioning
confidence: 93%
“…Also, other OPV infections are emerging. Monkeypox virus is responsible for increasing outbreaks in Democratic Republic of the Congo (55), and increasing zoonotic infections of vaccinia virus (VACV), as well as of buffalopox, are being observed in Brazil and in India (1,13,34,56). Similarly, emerging infections with cowpox virus (CPXV) are seen in humans and in domestic and zoo animals in Europe (9,25,35,36,49,64).…”
mentioning
confidence: 99%
“…However, this report and others of laboratory-acquired vaccinia infections showed that vaccination is being forgone in certain institutions. [678262728] No usual instructions exist for the level of precautions to be used by unvaccinated personnel. Vaccination may probably prevent or attenuate these patients’ infection, and it should continue to be recommended for laboratory workers who handle vaccinia.…”
Section: Discussionmentioning
confidence: 99%
“…reported laboratory-acquired VACV infection in a recently immunized person too that shows that handling of virus even by immunized people is also needed to employ special measures. [2728]…”
Section: Discussionmentioning
confidence: 99%